A note on the sample covariance from a bivariate normal population (Journal of Statistical Research, 2025)
Both the Moment Generating Function and the Probability Density Function of sample covariance based on a bivariate normal distribution have been presented in a simpler way by using conditional distributions. We also prove that the random variable sample covariance is a linear combination of two chi-square random variables if they are statistically independent.Journal of Statistical Research 2025, Vol. 59, No. 1, pp. 99-106